'Understanding things from within'. A Husserlian phenomenological approach to doing educational research and inquiring about learning. Issue 1 (1st January 2018) - Creely, Edwin
ABSTRACT: This article describes a phenomenological approach to doing educational inquiry and understanding learning. Working within the qualitative tradition, the research is conceived as 'narrow and deep', intimate research that focuses definitively on internality and on first-hand experiences of learning. The theoretical background for doing phenomenological research is explained, especially in regard to the ideas of Edmund Husserl. Then, the author's own systematic process for doing phenomenological research in education and exploring learning is offered with examples from his doctoral research project in which he investigated doctoral students and their experience of negotiating their learning. Samples from the author's writing in regard to one research participant are used to illustrate the research process explicated in the article.